THE RESULT OF VALIDATION TESTING AND STUDENTS RESPONSE TO GEOSCIENCE STUDENTS WORKSHEETS TO IMPROVE STUDENT SCIENTIFIC WORK AND CONCEPTUAL MASTERY - Febriani Sarwendah; Meida Wulan Sari; Icha Kurnia Wati (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2021)
Geoscience is a study of earth, it is easy to find around everyday students ;ife. The aim of this research is to develop Geoscience Students Worksheets based on scientific work to enhance students scientific work and conceptual mastery also to test the validity of the Geoscience Students Wroksheets through experts appraisal and students response. This reasearch is R & D research using 4D model until Develop stage. Data collection techniques including survey and interview technique. The question in the questionnaire consists on closed ended and open ended, the close ended question it to measure the validity and students response while open ended question for obtaining suggestions from all experts and students. Moreover, interview conducted during preliminary study. There are two validators in this research, they are content and learning media expert with Science Education educational background. In addition, ten students respondents in this research are already took the Geoscience Course last year. Quantitative data was analyzed by comparing the score with certain criteria and qualitative data was analyzed with finding common topics. Validation result and students respon results show that Geoscience Students Worksheets is very valid with score from content expert, learning media expert, and students consecutively 90,01%, 85,70%, and 89,4%.